Rancangan Manajemen Rantai Pasok Sapi Potong untuk Bisnis Sosial yang Berkelanjutan, Studi Kasus Program 'Tebar Hewan Kurban', 'Dompet Dhuafa Republika' - Zainal Abidin; Najmudin Najmudin; Iqbal Iqbal; Nurtania Sudarmi (SERAMBI: Jurnal Ekonomi Manajemen dan Bisnis Islam, 2022)
Highlighting community empowerment programs, this paper aims to develop a concept of a sustainable social business model based on sacrificial ritual activities, based on a case study of the Tebar Hewan Kurban (THK) program of Dompet Dhuafa Republika (DDR). Survey data from interviews with 120 THK partner beef cattle farmers outside Java and observations in the implementation of the THK program along the supply chain in 2020 are presented descriptively and qualitatively, then analyzed to get a better concept formulation. The results of this research are expected to provide solutions to various problems in the implementation of Qurbani to have a positive influence, both in the form of profits and or benefits to all stakeholders (farmers, farmer groups, capital owners, DDR, marketing partners, and beneficiaries of qurbani meat) involved in the program flow. In broader practice, the program flow is worth considering in similar programs at other institutions or in a more extensive scope (country). This paper contributes by filling a gap in the supply chain management literature, where empirical studies on programs to improve the welfare of marginalized communities associated with sacrificial rituals. Empowering farmers by involving stakeholders in the supply chain from upstream to downstream, which benefits all parties involved, is feasible for business sustainability